1998
DOI: 10.1111/j.1440-1673.1998.tb00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Are percutaneous transgastric biopsies using 14‐, 16‐ and 18‐G Tru‐Cut needles safe? An experimental study in the rabbit

Abstract: We evaluated perforation, peritonitis and bleeding after 14-, 16-, 18-G Tru-Cut needles were passed through the stomach in an animal model. Insertions were performed on seven anaesthetized rabbits with 18-, 16- and 14-G needles simulating the clinical technique. Diluted contrast medium with methylene blue (60 mL) was administered through a nasogastric tube after the biopsy. Computed tomography (CT) scanning of the upper abdomen was performed 10 min after the insertion for leakage. The abdominal contents were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…According to the literature, cutting needle biopsy is an efficient, rapid, and safe approach that offers sufficient biological tissue for the histopathological diagnosis and is used in the field of medicine which has to be further implemented in dentistry too. [ 17 18 19 20 21 ] A rabbit model study by Akan et al suggested that 14-, 16-, and 18- gauge cutting needles did not show any significant results whereas 18- and 20-gauge needles showed good results on hematoma by Yu et al [ 20 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, cutting needle biopsy is an efficient, rapid, and safe approach that offers sufficient biological tissue for the histopathological diagnosis and is used in the field of medicine which has to be further implemented in dentistry too. [ 17 18 19 20 21 ] A rabbit model study by Akan et al suggested that 14-, 16-, and 18- gauge cutting needles did not show any significant results whereas 18- and 20-gauge needles showed good results on hematoma by Yu et al [ 20 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, in dentistry it is necessary to develop more studies to evaluate the effectiveness of this technique [9]. Additionally, Akan et al [26] compared cutting needles of 14-, 16- and 18-gauge in rabbit's experimental studies, to verify the possible intraoperative complications caused by those needles; however, they did not find relevant results. In contrast, Yu et al [24] found that hematoma occurred in patients who were submitted to cutting biopsy with needle with 18- and 20-gauge.…”
Section: Discussionmentioning
confidence: 99%
“…The stomach is generally considered very low risk due to its thick wall and near sterility, with studies suggesting that needles as large as 18-gauge may be introduced without fear of peritonitis or bleeding. 57,58 The small bowel too is low risk, although smaller-gauge needles (20-to 22-gauge) are preferred. 28 By contrast, all attempts should be made to avoid the colon due to its high bacterial content, risk of peritonitis should spillage occur, and potential for contamination of the biopsy specimen.…”
Section: Techniquesmentioning
confidence: 99%